MENINGKATKAN EFEKTIVITAS LAYANAN BIMBINGAN DI SEKOLAH DASAR,STUDI KASUS SD GEMIT 027 MEBUNG - Vera Marta Kabey; Yolanda Laumai, Riflisrianly Beriledang, Yessy Mata, Petrus Mau Tellu Dony, Halena Muna Bekata (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
Guidance services in elementary schools play a strategic role in helping students cope with personal, social, and academic challenges. This study aims to describe the types of guidance services provided, common student issues, the role of teachers, implementation barriers, and strategies to improve the effectiveness of guidance services at SD GMIT 027 Mebung. Data were collected through an interview with a classroom teacher who has five years of teaching experience. The results indicate that guidance services are delivered informally and orally. The most frequent issue encountered among students is bullying behavior. Teachers act as role models and facilitators of students’ developmental stages; however, the implementation of guidance services is hindered by a lack of understanding regarding its concepts. To enhance effectiveness, collaboration among teachers, parents, and students is essential, along with the application of age-appropriate guidance methods. This study emphasizes the need to strengthen teachers’ capacities in delivering meaningful and sustainable guidance services in primary education.